Comparison of Pharyngeal Airway and Dentoskeletal Effects of 2 and 4 Premolar Extraction Treatment in Adult Orthodontic Patients - Genc, Esra; Karaman, Ahmet (Journal of Dentistry Indonesia, 2025)
Objective: This study aimed to compare pharyngeal airway and dentoskeletal effects of 2 and 4 premolar extraction treatments in adult patients separately for each gender. Methods: The study was conducted with 60 adults (26 males; 34 females) aged 18-35 years. Individuals were divided into 3 groups as non-extraction, 2-premolar extraction, and 4-premolar extraction. Pre-treatment (T0) and post-treatment (T1) dentoskeletal and pharyngeal airway measurements were performed on cephalometric radiographs. Results: A significant increase in nasopharyngeal airway (PNS-ad2) and anterior hyoid bone movement (CV3ai-H) was observed in the 4-extraction group; whereas in the 2-extraction group, inferior oropharyngeal airway (IAS) narrowing and hyoid bone movement in posterosuperior direction were observed. In the non-extraction group, inferior oropharyngeal airway narrowing and hyoid bone movement in the anteroinferior direction were observed. A significant increase in nasopharyngeal airway, narrowing of oropharyngeal airway, and superior hyoid bone movement were observed in the 2-extraction group in males. In the non-extraction and 4-extraction groups, the hyoid bone moved in inferior and anterior directions, respectively. While the hyoid bone moved posteriorly in the 2-extraction group in females, there was an increase in nasopharyngeal airway and narrowing of the middle oropharyngeal airway (MAS) in the 4-extraction group. Conclusion: While the nasopharyngeal airway was widened in individuals with 4-extractions, the inferior oropharyngeal airway was narrowed in both the 2-extraction and non-extraction groups. Hyoid bone movement was observed in anterior, posterosuperior, and anteroinferior directions in 4-extraction, 2-extraction, and non-extraction patients, respectively, and these changes vary according to gender.